Estudo das fases de pedras de rins de oxalato de cálcio monohidratado e determinação de uma nova forma polimórfica - Maifrede, Eduardo Bravim (2011)
This work describes a carefully crystallographic phase analysis presented in kidney stones using X ray powder diffraction technique. These kidney stones, donated by Vitória citizen, were cataloged and separate according with composition. Among the samples, one representative was classified as monophasic. This sample composed by monohydrated calcium oxalate was submitted to X ray Synchrotron Radiation at XPD beam (LNLS) - Campinas – Brasil. A Rietveld refinements were done taken into account the date from high resolution X ray synchrotron. The final result of this refinement indicated that calcium oxalate monohydrated is a new polymorphic phase as compared with ICCD CIF 30782, it was used as a input data in the Rietveld refinement as inicial. As conclusion, it was proposed here a new input date to describe this new polymorphic phase of Ca(CO2)(H2O).